Burmese/Malayan Spotted dove (Spilopelia chinensis tigrina) (Aves: Columbiformes) in rural and urban areas of Bangladesh - Ashraful Kabir (Journal of Wildlife, 2024)
In nature both rural and urban areas are significant for avian diversity. In Bangladesh, spotted dove (Spilopelia chinensis tigrina) is very common and widely distributed (Figure 1; Plates 1-2). If a bird is available in nature, we should try to find the reasons for their ultimate conservation. In this regard, this article could initiate to establish birds that are less in nature. At the time of journey, living in rural or urban and workplace helped to write this article on the availability and breeding of spotted dove. A pair of binoculars used to identify dove species. In addition, an android mobile phone and DSLR camera was helpful for sufficient snaps. Result suggested based on the dove species especially emphasized in four districts of Bangladesh―Kushtia, Rajshahi, Nilphamari, and Dinajpur. Out of 15 pairs and from 17 squab, the survival young were 9 (52.94%) (Table 1).
Keywords: Spotted Dove